The Effect of Performance Measurement Systems. Trust to Manager, and Job Satisfaction on Employee Performance - Maryani Maryani; Rindu Rika Gamayuni; Fajar Gustiawaty Dewi (Penerbit Goodwood, 2026)
Purpose: This study investigates how Performance Measurement Systems (PMS) influence employee performance in public sector organizations, focusing on the mediating roles of trust in managers and job satisfaction. Methodology/approach: A quantitative survey was conducted among employees of state-owned banks across eight provinces on Sumatra Island in Indonesia. The study used 200 valid responses and tested the hypothesized relationships through Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS. Results/findings: The results show that PMS significantly and positively impacted employee performance. Trust in managers and job satisfaction partially mediated this relationship, suggesting that PMS enhances performance through both formal controls and strengthens relational trust and work attitudes. Conclusions: The study concludes that PMS improves employee performance not only by providing formal control mechanisms but also by fostering trust and job satisfaction. Limitations: The cross-sectional design and sector-specific focus may limit the generalizability of these findings. Future studies could adopt longitudinal approaches or extend the model to other public sector contexts and emerging economies. Contributions: This study contributes to the public sector management literature by integrating control, trust, and attitudinal perspectives. It provides empirical evidence from an emerging economy and offers insights for public-sector managers on designing PMS that enhance both accountability and employee well-being.